Guidelines for the prevention of secondary lymphedema following breast cancer treatment: adhesion and associated factors - Fabro, Erica Alves Nogueira; Macedo, Flávia Oliveira; Costa, Rejane Medeiros; Lou, Marianna Brito de Araújo; Marchito, Liz de Oliveira; Aguiar, Suzana Sales de; Bergmann, Anke (Mastology, 2021)
Introduction: Lymphedema is the most feared complication that may take place after breast cancer treatment. With treatment progression, doubts have arisen regarding the real benefits of lymphedema prevention care, as well as of patient adherence to guidelines. Objective: In this context, the aim of this study was to assess patient adherence to preventive lymphedema guidelines and the distribution of sociodemographic, clinical, and treatment variables according to adherence to treatment. Methods: A cross‑sectional study conducted at the Cancer Hospital III/INCA, Rio de Janeiro, Brazil, concerning patients with breast cancer undergoing surgical treatment with an axillary approach. Participants were questioned about assistance care performance, exercise‑related care, and limb ipsilateral to surgery care. A descriptive analysis of patient demographic, clinical, treatments, postoperative complications variables, and main outcomes (adherence to the guidelines) was performed through a central tendency measure and data dispersion and frequency measures analyses. Differences between means were assessed using the Student’s t‑test, while differences between proportions were evaluated using the chi‑square test. A significance level of 5% was considered for all assessments. Results: Of the 103 women included in this study, 89.3% adhered to assistance care, 61.2% adhered to limb care, and 42.7% performed exercise‑related care. Women undergoing chemotherapy (p = 0.030) and axillary lymphadenectomy (AL) (p = 0.017) exhibited greater adherence to care. Non‑white patients (p = 0.048) and those who underwent AL (p = 0.025) adhered to limb care more frequently. Finally, patients displaying lower education levels (p = 0.013) and those who underwent AL (p = 0.009) adhered more frequently to limb exercises. Conclusion:Patients adhered the most to assistance care and limb care compared to exercise practice. Patients undergoing chemotherapy displayed greater adherence to care and non‑white patients adhered the most to limb care. Women who underwent AL displayed greater adherence to all types of care and those presenting lower education levels adhered more frequently to exercise guidelines.